Scanning transmission electron microscopic analysis of nitrogen generated by 3, 3′-diaminobenzidine-besed peroxidase reaction with resin ultrathin sections of rhinoceros parotid gland acinar cells. (12th November 2018) - Moriguchi, Keiichi; Jogahara, Takamichi; Oda, Senichi; Honda, Masaki
Abstract : We attempted to demonstrate the relationship between secretory granules (SGs) in resin ultrathin sections of Indian rhinoceros parotid gland acinar cells and endogenous peroxidase activity. The STEM mapping patterns of nitrogen generated by DAB reaction were restricted to the dense body of SG, ER, NE and several components of G. Abstract: A 3, 3′-diaminobenzidine (DAB)-based method was used to detect the localization of endogenous peroxidase activity in Indian rhinoceros ( Rhinoceros unicornis ) parotid gland acinar cells. The tissue had previously been resin-embedded in gelatin capsules for routine electron microscopic observations and thus pre-incubation for endogenous peroxidase analysis was not possible. We attempted to demonstrate the relationship between secretory granules (SGs) in resin ultrathin sections of Indian rhinoceros parotid gland acinar cells and endogenous peroxidase activity. A JEM 1400 Plus scanning transmission electron microscope (STEM) was used to conduct energy dispersive X-ray spectroscopy (EDS) analysis of the presence of nitrogen generated by the DAB reaction in bipartite structural SG consisting of a dense body (or core). The mapping patterns of nitrogen were restricted to the dense body. We observed nitrogen localized in the rough endoplasmic reticulum (ER), nuclear envelope (NE) and several components of the Golgi apparatus (G) of rhinoceros parotid gland acinar cells participating in the synthetic pathway of secretory proteins. Moreover, we established a nitrogen-detection method by EDS analysis of rhinoceros parotid gland. The reliability of the method was validated by comparison of the test group (peroxidase detection in ultrathin resin sections) and the control group (ordinary peroxidase detection in semi-thin sections following glutaraldehyde pre-fixation) of rat submandibular gland. The same mapping patterns of nitrogen were detected by DAB reaction in the SG, ER, NE and G in these two groups. Hence, EDS-STEM approaches for endogenous peroxidase post-incubation analysis will prove useful for advanced cytochemical analysis for the identification of any other resin sections.